Curbing Carbon: An Experiment on Uncertainty and Information about CO₂ emissions - Davide Pace; Joël van der Weele (Tinbergen Institute, 2020)
We investigate how consumers respond to uncertainty about CO2 emission size. In an incentivized online experiment, participants can acquire a valuable good that emits an unknown amount of CO2. We find that beliefs about emission size are strongly predictive of purchases, even exceeding the effect of substantial changes in the price of the good. Moreover, information that makes beliefs more precise causes a 26% reduction in overall emissions, even though average beliefs are unchanged. The reduction occurs as the marginal willingness to pay for emission reduction declines with emission size, so people who are too optimistic about emissions are more responsive to information. We also test for the formation of self-serving beliefs. Contrary to theories of motivated reasoning, increasing the surplus from buying the product does not change patterns of attention or belief formation about emissions. Overall, the results suggest that information about CO2 impact can be an important policy lever, and that willingness-to-pay for emission reductions should take into account the size of emissions.
Keywords: Q54; C91; D81; 330; CO2 emissions; sustainable consumption; economic experiments